Nurturing resilient future citizens through value consistency vs. the retreat from multiculturalism and securitisation in the promotion of British values in schools in the UK. Issue 8 (17th November 2017) - McGhee, Derek; Zhang, Shaoying
Abstract: The controversial duty to promote British values in Schools and Further Education Colleges in England, Scotland and Wales was introduced in the Counter-Terrorism and Security Act 2015. This duty is described by some as the introduction of securitising mechanism into British Schools, for others it is a symptom of the UK Government's further retreat from Multiculturalism. In this article, we present the duty as the most recent reconstructive intervention designed to remedy alleged failings in the education system to produce liberal British citizens and to counter the growth of extremism. In the article, we will explore how local institutions such as schools and colleges have implemented the duty in a way that defuses some of the securitising aspects of the Statutory Duty through celebrating the UK as a multi-racial, multi-faith and multi-cultural society and through ensuring that their promotion of British values is consistent with their existing value system and ethos which includes the promotion of pupils' Spiritual, Moral, Social and Cultural Development.